Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00431-018-3194-y
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of adverse events in low-risk non-survivors in pediatric intensive care patients: an exploratory study

Abstract: We studied the occurrence of adverse events (AEs) in low-risk non-survivors (LNs), compared to low-risk survivors (LSs), high-risk non-survivors (HNs), and high-risk survivors (HSs) in two pediatric intensive care units (PICUs). The study was performed as a retrospective patient record review study, using a PICU-trigger tool. A random sample of 48 PICU patients (0–18 years) was chosen, stratified into four subgroups of 12 patients: LNs, LSs, HNs, and HSs. Primary outcome was the occurrence of AEs. The severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…The findings revealed a low incidence rate of AEs, about 11%, in all of the examined patient rooms. This is a lower incidence than what prior research has reported, 2‐4 also in Swedish settings of critical care 41,42 . There were no findings in this study that indicated that the intervention room had any significant effect on decreasing the number of AEs for the critically ill patients assigned to the refurbished room.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The findings revealed a low incidence rate of AEs, about 11%, in all of the examined patient rooms. This is a lower incidence than what prior research has reported, 2‐4 also in Swedish settings of critical care 41,42 . There were no findings in this study that indicated that the intervention room had any significant effect on decreasing the number of AEs for the critically ill patients assigned to the refurbished room.…”
Section: Discussioncontrasting
confidence: 76%
“…An AE is defined as an injury related to medical management that may be either preventable or non‐preventable 1 . Unfortunately, AEs are relatively common with incidence rates ranging from 29% to 83% in intensive care settings, 2‐4 and they have serious consequences, including death, among already vulnerable patients with life‐threatening conditions. However, AEs are often preventable, and an improved healthcare environment could support and reduce the number of AEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sample size was larger than in similar studies of specific patient cohorts [ 44 46 ] but smaller than in previous work focused on general hospital populations, where a smaller proportion of deaths were anticipated to be modifiable [ 9 , 11 ]. As a result, our estimates of the rates of avoidable deaths have relatively wide confidence intervals.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, the contribution of AEs in these “unexpected deaths” is unknown but of great interest. Although one may expect that AEs mainly occur in the most complex, critically ill PICU patients, two small studies showed that low-risk PICU patients who die have a high occurrence of AEs ( 14 , 15 ). In order to gain more insight into the occurrence and relevance of AEs in low-risk PICU nonsurvivors, we performed a nation-wide study in The Netherlands.…”
mentioning
confidence: 99%